Pengaruh Partisipasi Anggaran Terhadap Kinerja Manajerial Dengan Komitmen Organisasi Sebagai Variabel Moderating - Iriany Dewi Soleiman; Juleha Hasan; Nuraini Ismail (STIE AMKOP, 2023)
The purpose of this study is to find empirical evidence whether there is an effect of budgetary participation on managerial performance at the Ende District Work Units in relation to organizational commitment as moderating variables. The inconsistency of the results from previous studies motivates researchers to raise the topic of this research again. In this study the data were obtained by distributing questionnaires to managers in the regional work units of Ende district who were involved in budgeting activity. From 159 questionnaires, only 61 completed questionnaires return and could be processed. This research was conducted using the SPSS version 21.00.The statistical method used to test the hypothesis is simple regression mode, multiple regression and moderated regression analysis. Before testing the hypothesis, the data quality was tested first and classical assumptions was conducted. The results of this reserach indicate that budgetary participation affects managerial performance with a significance level 0,000,005 .Future research is expected to add other variables which affect managerial performance. Keywords: Budgeting Participation, Organizational Commitment, Managerial Performance